The Effectiveness of Tax Education in Improving Compliance and Achieving Tax Revenue Targets at The Sidoarjo Selatan Primary Tax Office - Nuzulul Widyatmo Nugroho; Sri Rahayu; Anita Kartika Sari (Neo Journal of economy and social humanities, 2026)
This study aims to analyze the effect of tax socialization, tax officer competence, and the quality of tax education materials on taxpayer compliance and the achievement of tax revenue targets at the South Sidoarjo Tax Office. This research used a quantitative approach with a survey method. Data were collected by distributing questionnaires to 150 respondents and analyzed using multiple linear regression through two models. The first model examined the effect of the independent variables on taxpayer compliance, while the second model examined their effect on tax revenue targets. The results show that tax socialization, tax officer competence, and the quality of tax education materials partially have a positive and significant effect on taxpayer compliance. These three variables also have a positive and significant effect on the achievement of tax revenue targets. Simultaneously, tax socialization, tax officer competence, and the quality of tax education materials significantly affect taxpayer compliance and tax revenue targets.